A qPCR MGB probe based eDNA assay for European freshwater pearl mussel (Margaritifera margaritifera L.). Issue 6 (12th July 2017) - Carlsson, Jeanette E.L.; Egan, Damian; Collins, Patrick C.; Farrell, Edward D.; Igoe, Fran; Carlsson, Jens
Abstract: 1. Environmental (e)DNA assays are becoming increasingly used to detect rare or invasive aquatic species. 2. The Critically Endangered freshwater pearl mussel Margaritifera margaritifera is undergoing range‐wide reduction in population numbers and distribution. 3. An eDNA assay to detect the presence of M. margaritifera was developed, based on the mitochondrial cytochrome oxidase I gene, utilizing species‐specific primers, a minor groove binding (MGB) probe and quantitative (q)PCR approaches. 4. The results from this pilot study demonstrated high sensitivity both in laboratory and field trials, and provide a valuable non‐invasive tool for detecting M. margaritifera .